Environmental Sensitivity of Teacher Education Students in the Earthquake Zone - Karacaoğlu, Ömer Cem; Özkaya, Abdulkadir (CV. Literasi Indonesia, 2023)
The research aimed to assess the environmental sensitivity of teacher education students within an earthquake-prone region, specifically exploring potential correlations between their environmental awareness, settlement size, educational program, and experiences related to the February 6 Earthquake. 342 students from Hatay Mustafa Kemal University Faculty of Education participated in the study, employing quantitative research methods and the “Environmental Sensitivity Questionnaire”. Data analysis involved frequency, arithmetic mean, and percentages, with the Kruskal-Wallis H test used to examine the link between students' environmental sensitivity, program of study, and settlement size, and the Mann-Whitney U test employed to assess the association between experiencing the February 6 Earthquake and environmental sensitivity. The data were analyzed using the SPSS program. The findings revealed that teacher-education students exhibited partial environmental sensitivity. Notably, students enrolled in mathematics teaching programs displayed higher environmental sensitivity than those in social studies teaching programs, while students residing in metropolitan and urban areas exhibited greater environmental awareness than their counterparts in non-metropolitan areas. Moreover, the research highlighted that teacher education students in earthquake-prone regions exhibited partial sensitivity towards air and water pollution, with lower sensitivity regarding soil pollution, population planning, and engagement in environmental initiatives.